2016
DOI: 10.1016/j.ejrad.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the guidelines of paediatric cervical spine clearance in a level I trauma centre: A single centre experience

Abstract: The adherence to the international guidelines when to obtain radiographic imaging was 100%. However, in a large proportion of patients (56%), not the recommended number of radiographs was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…These data correspond with the findings of previous studies-performed both in level 1 trauma centres and other hospitals-which have also reported low incidences. The incidence varies from 0.3-3.7%, depending on the specific population studied [4][5][6][7]28]. Our study confirms that a child presenting at a level 2 trauma centre after blunt trauma is very unlikely to have relevant C-spine injury.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…These data correspond with the findings of previous studies-performed both in level 1 trauma centres and other hospitals-which have also reported low incidences. The incidence varies from 0.3-3.7%, depending on the specific population studied [4][5][6][7]28]. Our study confirms that a child presenting at a level 2 trauma centre after blunt trauma is very unlikely to have relevant C-spine injury.…”
Section: Discussionsupporting
confidence: 69%
“…With regard to the indication for imaging, adherence to our initial and updated in-hospital protocol was high. A study by Slaar et al in a level 1 trauma centre also found that Dutch physicians generally do adhere to the guidelines in terms of which children require imaging [4]. Nevertheless, radiologic imaging could have been avoided in at least ten percent of our patients if the protocols had been followed in all cases.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Traditionally, it has been thought that there is a lack of adherence to medical imaging referral guidelines by referrers 22 . However, there is specific evidence that paediatric trauma medical imaging guidelines in the ED can have excellent compliance rates 19,28 . McGrew and colleagues have clearly shown that in a level II paediatric trauma centre, the implementation of evidence based CT guidelines for paediatric trauma reduced CT rates by 16% without a difference in outcome 29 …”
Section: Discussionmentioning
confidence: 99%